Biofortification of durum wheat with zinc and iron - Cakmak, Ismail; Pfeiffer, Wolfgang H.; McClafferty, Bonnie F. (Wiley, 2010)
Micronutrient malnutrition affects over 2 billion people in the developing world. Iron (Fe) deficiency alone affects >47% of all preschool aged children globally, often leading to impaired physical growth, mental development, and learning capacity. Zinc (Zn) deficiency, like iron, is thought to affect billions of people, hampering growth and development, and destroying immune systems. In many micronutrient‐deficient regions, wheat is the dominant staple food making up >50% of the diet. Biofortification, or harnessing the powers of plant breeding to improve the nutritional quality of foods, is a new approach being used to improve the nutrient content of a variety of staple crops. Durum wheat in particular has been quite responsive to breeding for nutritional quality by making full use of the genetic diversity of Fe and Zn concentrations in wild and synthetic parents. Micronutrient concentration and genetic diversity has been well explored under the HarvestPlus biofortification research program, and very positive associations have been confirmed between grain concentrations of protein, Zn, and Fe. Yet some work remains to adequately explain genetic control and molecular mechanisms affecting the accumulation of Zn and Fe in grain. Further, evidence suggests that nitrogen (N) nutritional status of plants can have a positive impact on root uptake and the deposition of micronutrients in seed. Extensive research has been completed on the role of Zn fertilizers in increasing the Zn density of grain, suggesting that where fertilizers are available, making full use of Zn fertilizers can provide an immediate and effective option to increase grain Zn concentration, and productivity in particular, under soil conditions with severe Zn deficiency.